1999
DOI: 10.1097/00000658-199908000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Level I and II Axillary Dissection in the Treatment of Carcinoma of the Breast

Abstract: ObjectiveTo assess the complications of level I and II axillary lymph node dissection in the treatment of stage I and II breast cancer, with breast-conservation surgery and mastectomy. Summary Background DataThe role of axillary dissection for staging, and as an effective means of controlling regional nodal disease, has long been recognized. As small and low-grade lesions have been detected more frequently, and as its therapeutic impact has been questioned, axillary dissection has increasingly been perceived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(87 citation statements)
references
References 37 publications
2
83
0
2
Order By: Relevance
“…3 This surgical procedure causes local morbidity, resulting in lymphocele, pain, limited shoulder movement and upper limb lymphedema. 4 Axillary sentinel lymph node (ASLN) resection is an alternative to lymphadenectomy. 5 The morbidity related to ASLN resection is significantly less compared with the morbidity related to axillary lymphadenectomy.…”
mentioning
confidence: 99%
“…3 This surgical procedure causes local morbidity, resulting in lymphocele, pain, limited shoulder movement and upper limb lymphedema. 4 Axillary sentinel lymph node (ASLN) resection is an alternative to lymphadenectomy. 5 The morbidity related to ASLN resection is significantly less compared with the morbidity related to axillary lymphadenectomy.…”
mentioning
confidence: 99%
“…Meanwhile, malignant process caused by the infiltration of the tumor cells causes distortion and destruction on the structure of the lymph node blood vessel [27]. Malignant tumor itself, generally, stimulates neovascularization, in terms of the secretion of angiogenesis factors [28][29] [30]. The imaging of malignant lymph nodes, according to Tschammler et al, showed that there were four types of distortion angioarchitecture distortion, namely (1) encasement indicated by the curved forms of some of the intranodal blood vessels; (2) aberrant vessels indicated by one or more central blood vessels that formed an angle of more than 30 0 with longitudinal lymph node axis; (3) the disappearance of the focal perfusion indicated by the disappearance of the signal flows of the blood vessels in the lymph nodes when hypervascularization occurred in the surrounding tissues; and (4) sub-capsular blood vessels indicated by short blood vessels located in the peripheral lymph nodes, which were not derived from either hilus or longitudinal blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Although axillary surgery staging, with or without breast conservation techniques, is considered relatively free from significant complications, a postoperative study of 200 patients suggested that lymphatic complications may still occur [12].…”
Section: Primary and Secondary Lymphoedemamentioning
confidence: 99%